Investigation of the role of the extracellular β-agarase, produced by the bacterial epiphyte Pseudoalteromonas sp. LS2i, in the virulence response towards the agarophyte Gracilaria gracilis - Gildenhuys, Carin (Department of Molecular and Cell Biology, 2014)
Includes abstract